HOW ORGANIZATION PERFORMANCE DIFFER FROM KOREAN AND MALAYSIAN INFORMATION TECHNOLOGY (IT) COMPANIES? - Hyun, Kwan-Song; Abdul Wahab, Shah Rollah; Shin, Tack-Hyun (Journal of Human Capital Development (JHCD), 2020)
The main purpose of this study is to highlight the interaction effect between ’market orientation’ which is recognized as a sustainable competitive advantage factor in the private sector and ‘environmental turbulence’ on the marketing capabilities which is one of the powerful antecedents of organizational performance, contrasting the IT companies in Korea and Malaysia believed to exist a certain difference in the capitalistic market economy system. It was found that there exists sharp contrast between two countries in that Korea showed a significant interaction effect between customer orientation and environmental turbulence, however, Malaysia showed no significant moderation effect. This result may implicate the difference in the process of market mechanism and environmental turbulence between the two countries.